PENINGKATAN KETERAMPILAN BERBICARA DENGAN MEDIA GAMBAR SERI DI KELAS II SDN 03 SIMPANG KECAMATAN KOTO XI TARUSAN KAB. PESISIR SELATAN - Erna Erna M (JURNAL MANAJEMEN PENDIDIKAN, 2018)
ABSTRACT This study aims to describe the improvement of speaking skills through a series of media images in class II SDN 03 Simpang Kec. Koto XI Tarusan Kab. South Coast. The opinions used as reference are Nurhadi (1995) and Wina Sanjaya (2006) for speaking skills, series drawing media by Sudirman (2003) and Arsyad (2006), argued Arikunto (2010) to analyze data. This type of research is classroom action research (CAR). Research subjects were 15 students. The study was conducted in 2 cycles and each cycle consisted of 2 meetings. The results of the study found an increase in students' speaking skills in the first cycle of 51.1 and in the second cycle increased by 75.6 percent in completeness of student learning outcomes in the first cycle 46.66% and in the second cycle 80%. Thus, the use of serial image media can improve students' speaking skills. Therefore, it is recommended for teachers to be able to use the serial drawing media in Indonesian language learning in elementary school. Keywords: Speech Absence, Indonesian Language Media